Ճենաց աշխարհի եւ Մամիկոնյան նախարարական տոհմի ծագման հարցի շուրջ - Լավրենտի Հովհաննիսյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В "Истории Армении" Мовсеса Хоренаци происхождение княжеского рода Мамиконянов связывается с именем некоего Мамгуна, прибывшего в Армению из "страны Ченов". В "Географии" того же автора описываются некоторые ее особенности. По мнению большинства исследователей, "страна Ченов" — Китай, а сами "чены" — китайцы. Эта гипотеза опровергается в статье в результате анализа ряда фактов. In Movses Khorenatsi's "Armenian history" the origin of Mamikonyan's princely House is connected with the name of Mamgun, who had come to Armenia from the Ճենաց (C'enac') country. In the "Geography" of the same author are described some specifities of the country. By the opinion of the most researchers the country of the Ճենաց is China and ճենք are cheenes. In the article basing on different facts and arguments this hypothesis is denied.
Keywords: History; Auxiliary Sciences of History; Genealogy